2021
DOI: 10.52006/main.v4i3.391
|View full text |Cite
|
Sign up to set email alerts
|

Printed Modular Distance Learning in Philippine Public Elementary Schools in Time of COVID-19 Pandemic: Quality, Implementation, and Challenges

Abstract: Coronavirus Disease 2019 forced educational sectors worldwide to implement various distance learning modalities. In the Philippines, printed modular distance learning modality was implemented to continue delivering quality and relevant education amid the pandemic. Thus, this study assessed the quality and implementation of PMDL in public elementary schools. Likewise, this study ranked the challenges encountered by the teachers in the quality and implementation of PMDL. Using descriptive and inferential analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…At the same time, their professors were moderately helpful in providing support and understanding while engaging in this learning arrangement. Talimodao and Madrigal (2021) assessed the 377 public elementary school teachers' perception of the quality and implementation of the printed modular distance learning (PMDL). The results revealed that teachers perceived that PMDL was consistently excellent, indicating its adherence to the national standards set by the governing agency.…”
Section: Related Researchmentioning
confidence: 99%
“…At the same time, their professors were moderately helpful in providing support and understanding while engaging in this learning arrangement. Talimodao and Madrigal (2021) assessed the 377 public elementary school teachers' perception of the quality and implementation of the printed modular distance learning (PMDL). The results revealed that teachers perceived that PMDL was consistently excellent, indicating its adherence to the national standards set by the governing agency.…”
Section: Related Researchmentioning
confidence: 99%
“…In learning motivation, studies were conducted in public high schools [22,18], private schools [23], and state universities and colleges [24,25]. In learning challenges, studies were conducted among public elementary and secondary school students [26,27,19]. However, given the available studies, there has been limited literature on learning environments, motivation, and challenges, especially in learning physical education among Philippine public high school students.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of students' learning perception, a study was conducted among senior high school students on philosophy [22]. Moreover, several studies were conducted during the pandemic, particularly on the implementation of distance learning [23,24]. Considering the available studies, there is a dearth of literature on students' motivation and perception, especially in learning social science amid a pandemic.…”
Section: Introductionmentioning
confidence: 99%